HYPEREUTECTIC SILUMIN.NANOSTRUCTURAL PROCESSES OF MELTING AND MOULDING - V. Yu. Stetsenko (Литьë и металлургия, 2017)
It is shown that melting and molding of hypereutectic silumin are complicated physical and chemical nanostructural processes. The major part at these processes is played by the centers of crystallization of primary crystals of silicon, silicon nanocrystals, the dissolved and adsorbed oxygen. The part of the modifying crystals of Cu3P is reduced to decreasing of concentration of the adsorbed oxygen and an intensification of process of coagulation of nanocrystals of silicon in the centers of crystallization of primary crystals of silicon.